Fabrication and testing of nano silver-coated filters for water treatment - Heidarpour, Farideh (2010)
As adequate freshwater supplies decrease steadily, novel technologies are required for water purification. Nanotechnology, a new scientific frontier, promises to revolutionize innovation in many industries. Advancements in nanotechnology are being applied in the water-purification industry, to keep harmful bacteria out of drinking water. Nano silver is used in many products as an antibacterial function due to its bactericidal properties. This study aimed to produce and investigate the effect of a nano silver coated water filter using polypropylene filter (NSF) via the physical vapor deposition method. The production of nano silver filter is used the modified Balzers 760 machine which was equipped with an electron beam gun ESQ 110. The nano-silver particles were made by electron beam bombardment of the silver metal, which were subsequently deposited on the polypropylene filter evenly. The thicknesses of the nano layer coated on the filters were about 35.0nm, 45.0nm and 55.0nm in average. Nano layer pore sizes, thicknesses, and crystallographic structure were determined by scanning electron microscopy (SEM), atomic force microscopy (AFM) and the X-ray diffraction technique (XRD) respectively. The water inoculated about 103cfu/ml Escherichia coli. The inductively coupled plasma/mass spectrometry (ICP/MS) was used to determine amount of silver nano-particles in water sample after filtration. The results showed that the count of nano silver particles in the filtered water sample was nil. At a flow rate of 3L/hr and after 6hour filtration 100% bacteria were removed for 55nm nano silver coated filter (NSF) and more than 99% Escherichia coli were inactivated for 45nm, and 35nm NSF, when the input water had a bacterial load of 103 colony-forming units (CFU) per mL. SEM photos revealed the present of filtered bacteria on the nano silver filter (NSF) after passing through the polluted water. Furthermore, the percent of removed bacteria increases with increasing removal time but decreases with increasing water flow rate. The filter system produced in this work has the potential to be used as an efficient water treatment method.